Does International Financial Integration Increase the Standard of Living in Africa? A Frontier Approach - (:unkn) unknown (My University, 2019)
We investigate whether a higher financial integration with the rest of the world can help the African countries reduce their production inefficiency and/or push up their efficient frontier of production. We use two alternative empirical approaches based, respectively, on a stochastic frontier analysis and quantile regressions. We provide evidence of heterogeneous situations across countries and time. This paper proposes a new approach for defining, at the aggregate level, a link between financial openness and production efficiency. We show that one size does not fit all: international financial integration can increase or decrease African countries' standard of living.
Keywords: African Research